Description of the female and variation in males of the critically endangered Caledargiolestes janiceae Lieftinck, 1975 from South New Caledonia (Odonata: Zygoptera: Argiolestidae) - Stenger, Pierre-Louis; Theuerkauf, Jörn; Mille, Christian G.; Jourdan, Hervé; Marinov, Milen (Zootaxa, 2024)
Caledargiolestes janiceae Lieftinck, 1975 was erected on the basis of a single not-fully mature male. Eleven years later a female was captured but never described. Despite further searching, this species was only rediscovered in early 2022 with one female and two males (immature and mature) collected. This paper provides descriptions of the female and of the male in different stages of maturity.